How Can We Measure the Magnitude of Creative Cities? A New Creativity Index: 3Ci. Issue 2 (2nd April 2020) - Yum, Seungil
ABSTRACT: There is some doubt about the effect of creative class on economic development. There is also concern that the 3Ts index (Talent, Technology, and Tolerance) does not take into account two of the most important elements of creativity into its index: creative infrastructure and culture. The present study proposed a new creativity index called 3Ci (Creative class, Creative infrastructure, and Culture) and explored how they played an important role in economic development across countries through a systematic literature review and econometric models. The present study found that creative class played a different role in economic development across articles and countries and all 35 articles in the present study suggested creative infrastructure and culture as two of the most important factors for creativity. The present study also highlighted that creative class, creative infrastructure, and culture were positively related to economic development in all US Metropolitan Statistical Areas and they should be considered when measuring the magnitude of creative cities.